THE FIGURE OF THE TABIB AND TYPES OF HEALING IN THE WORLDVIEW OF THE SURKHAN VALLEY POPULATION - Karimov Yusufjon Sherali oglu (American Journals Publishing, 2025)
This article provides an ethnographic analysis of the figure of the healer (tabib) and the types of folk medicine within the traditional worldview of the population of the Surxon Oasis. The study examines the formation of healing practices, the master–apprentice tradition, and significant customs such as “qo‘l olish” (initiation), the chilla ritual, and related rites. In addition, the healing methods employed by domlas, qushnochs, and healers—such as qaytarma, alaslash, kitob ochirish, boqin, and qoqin—are described on the basis of local field materials. The article reveals the close interconnection of folk medicine forms preserved in the Surxon Oasis with religious beliefs, superstitions, and ritual elements, and substantiates their socio-cultural significance in the life of society. The research findings are of considerable scholarly importance for the study of regional ethnography, folk medicine, and systems of traditional knowledge.
Keywords: Surxon Oasis, folk medicine, healer (tabib), domla, qushnoch, chilla, qaytarma, alaslash, boqin, qoqin, traditional worldview, ethnography